The Role of a Nonribosomal Peptide Synthetase in l‐Lysine Lactamization During Capuramycin Biosynthesis. (18th March 2016) - Liu, Xiaodong; Jin, Yuanyuan; Cui, Zheng; Nonaka, Koichi; Baba, Satoshi; Funabashi, Masanori; Yang, Zhaoyong; Van Lanen, Steven G.
Abstract: Capuramycins are one of several known classes of natural products that contain anl ‐Lys‐derivedl ‐α‐amino‐ɛ‐caprolactam (l ‐ACL) unit. The α‐amino group ofl ‐ACL in a capuramycin is linked to an unsaturated hexuronic acid component through an amide bond that was previously shown to originate by an ATP‐independent enzymatic route. With the aid of a combined in vivo and in vitro approach, a predicted tridomain nonribosomal peptide synthetase CapU is functionally characterized here as the ATP‐dependent amide‐bond‐forming catalyst responsible for the biosynthesis of the remaining amide bond present inl ‐ACL. The results are consistent with the adenylation domain of CapU as the essential catalytic component forl ‐Lys activation and thioesterification of the adjacent thiolation domain. However, in contrast to expectations, lactamization does not require any additional domains or proteins and is likely a nonenzymatic event. The results set the stage for examining whether a similar NRPS‐mediated mechanism is employed in the biosynthesis of otherl ‐ACL‐containing natural products and, just as intriguingly, how spontaneous lactamization is avoided in the numerous NRPS‐derived peptides that contain an unmodifiedl ‐Lys residue. Abstract : Aminocaprolactams in natural products : The biosynthetic mechanism for producing the aminocaprolactam moiety in the capuramycin anti‐mycobacterial antibiotics was delineated by using a combined in vivo and in vitro approach. The process is initiated by adenylation and thioesterification ofl ‐Lys and characterized by an apparently nonenzymatic intramolecular lactamization.